A feedback technique for unsatisfiable UML/OCL class diagrams. (24th June 2013) - Shaikh, Asadullah; Wiil, Uffe Kock
SUMMARY In Model‐Driven Development (MDD), detection of model defects is necessary for correct model transformations. Formal verification tools and techniques can to some extent verify models. However, scalability is a serious issue in relation to verification of complex UML/OCL class diagrams. We have proposed a model slicing technique that slices the original model into submodels to address the scalability issue. A submodel can be detected as unsatisfiable if there are no valid values for one or more attributes of an object in the diagram or if the submodel provides inconsistent conditions on the number of objects of a given type. In this paper, we propose a novel feedback technique through model slicing that detects unsatisfiable submodels and their integrity constraints among the complex hierarchy of an entire UML/OCL class diagram. The software developers can therefore focus their revision efforts on the incorrect submodels while ignoring the rest of the model. Copyright © 2013 John Wiley & Sons, Ltd.